Toxic bait abandonment by an invasive ant is driven by aversive memories - Daniel Zanola; Tomer J. Czaczkes; Roxana Josens (Communications Biology)
Abstract Social insects such as ants possess a battery of behavioural mechanisms protecting their colonies against pathogens and toxins. Recently, active abandonment of poisoned food was described in the invasive ant Linepithema humile. During this abandonment, foraging declines by 80% within 6–8 h after baits become toxic—a reduction not due to satiety, diminished motivation, or mortality. Here we explore the mechanisms behind this behaviour, testing two hypotheses: (1) the presence of ‘no entry’ pheromones near toxic food, and (2) the formation of aversive memories linked to the toxic food site. In field trials, we placed bridges leading to sucrose, nothing, or poisoned sucrose on an active trail. Within hours, 80% of ants abandoned poisoned bait bridges. By swapping bridges strategically, we confirmed that aversive memories formed at toxic bait sites, while no evidence of a ‘no entry’ pheromone was found. Then, in the laboratory, we asked how ants may be sensing the toxicity of the bait, hypothesising poison-induced malaise. Motility, used as a proxy for malaise, was 29% lower in toxicant-exposed ants after 3 h, linking malaise to abandonment. Developing toxicants with delayed malaise, not just delayed mortality, may improve toxic bait control protocols.